2022
DOI: 10.1093/ndt/gfac128
|View full text |Cite
|
Sign up to set email alerts
|

Bone density, microarchitecture and estimated strength in stone formers: a cross-sectional HR-pQCT study

Abstract: Background Low areal bone mineral density (BMD), increased fracture risk, and altered bone remodelling have been described among stone formers (SF), but the magnitude of these findings differs by age, sex, menopausal status, and urinary calcium (uCa). This study aimed to investigate volumetric (v) BMD, bone microarchitecture and biomechanical properties by high-resolution peripheral quantitative computed tomography (HR-pQCT) and finite element analysis (FEA) in young SF, irrespective of calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Despite the well-known association of low BMD with hypercalciuria, as suggested by most studies [6,10,29], it still remains a controversial matter as many investigators have reported low BMD among normocalciuric individuals as well [12], which is in agreement with the present findings of a lack of differences in BMD according to the levels of calciuria. In a very recent cross-sectional study of our group employing HRpQCT in SFs, Esper et al [11] observed a reduced trabecular number (Tb.N) and volumetric BMD, indicating trabecular bone microarchitecture impairment, especially among women, as well as reduced bone strength parameters in men. Interestingly, they observed through a multivariate analysis an independent association of Tb.N with urinary calcium only at the distal radius, although BMI was a strong predictor of Tb.N at both radius and tibia.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Despite the well-known association of low BMD with hypercalciuria, as suggested by most studies [6,10,29], it still remains a controversial matter as many investigators have reported low BMD among normocalciuric individuals as well [12], which is in agreement with the present findings of a lack of differences in BMD according to the levels of calciuria. In a very recent cross-sectional study of our group employing HRpQCT in SFs, Esper et al [11] observed a reduced trabecular number (Tb.N) and volumetric BMD, indicating trabecular bone microarchitecture impairment, especially among women, as well as reduced bone strength parameters in men. Interestingly, they observed through a multivariate analysis an independent association of Tb.N with urinary calcium only at the distal radius, although BMI was a strong predictor of Tb.N at both radius and tibia.…”
Section: Discussionmentioning
confidence: 86%
“…Stone formers (SFs) exhibit reduced bone mineral density (BMD) [6,7], and previous histomorphometric studies have evidenced low bone formation and increased bone resorption [8,9]. Although bone demineralization occurs mostly in SFs with idiopathic hypercalciuria [8][9][10], it may be detected in normocalciuric SFs as well [11,12].…”
Section: Ofmentioning
confidence: 99%
“…Nephrolithiasis was systematically associated with low bone mineral density [ 12 , 13 ] and increased fracture risk [ 67 ], and previous histomorphometric analysis by our group showed high bone resorption and a mineralization defect [ 16 , 17 ]. More recently, we detected trabecular bone impairment and reduced bone strength by HR-pQCT in SF when compared to healthy controls [ 21 ]. Here, the subgroup of patients with higher VC (AAC > 5.8%) also exhibited significantly higher tibial cortical porosity, which may be consequent to bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…This study is a post hoc analysis of a prospective cohort that evaluated bone microarchitecture parameters by high-resolution peripheral quantitative computed tomography (HR-pQCT) in young SF [ 21 ]. The initial sample underwent nonenhanced computed tomography (CT) scans and full metabolic evaluation as a routine care at the nephrolithiasis outpatient clinic of the Nephrology Division of Universidade Federal de São Paulo (UNIFESP).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation